Sexual and Reproductive Health of Rohingya Refugees In Bangladesh: A Systematic Review - Hossain, Muhammad Anwar; Sawleshwarkar, Shailendra; Zablotska-Manos, Iryna (Women, Midwives and Midwifery, 2025)
Introduction: The Rohingya refugees in Bangladesh, a severely persecuted ethnic minority of Myanmar, face numerous challenges related to their sexual and reproductive health (SRH), including access to appropriate services. This systematic review examines the SRH status of Rohingya refugee women in Bangladesh, focusing on barriers to accessing SRH services and interventions to address their specific SRH needs. Methods: Following PRISMA guidelines, a systematic search was conducted across databases, including PubMed, CINAHL, Embase, Web of Science, and Scopus, as well as gray literature, from August 2017 to July 2023. Both quantitative and qualitative studies were included, with data extraction and analysis performed independently by two authors using a narrative synthesis approach. Results: Out of 394 citations, ten studies met the criteria. The findings revealed that 48.9% of Rohingya women were unaware of SRH service access, only 11% received frequent (once fortnightly) visits by family planning personnel, 70% lacked knowledge about HIV/STIs, and over two-thirds believed that family planning required husband approval. The prevalence of contraceptive use was 50.9%, with cultural and religious beliefs and gender dynamics significantly influencing family size decisions. Discussion: Cultural preferences impacted family size decisions, and limited awareness of permanent birth control widened the SRH education gap. The review emphasizes the need for comprehensive, community-based interventions, including door-to-door visits, culturally tailored outreach programs, and SRH education within refugee camps. To address the SRH needs of Rohingya women, adopting a multifaceted approach that promotes SRH education, improves service accessibility, and empowers women to make informed reproductive choices is essential.